Discussion of the relationship to nature and technology in Judaism, Christianity, and Islam - Hermanni, Friedrich 1958- (2001)
The Jewish religion does indeed assume that the world was created by God, but it nevertheless believes that human beings are free to act both rightly and wrongly. Thus, the idea of a Creator God does not imply determinism in Judaism. How is the relationship between freedom and creation seen in Indian Christianity? (Brumlik)